Taxonomy, ecology and geographic distribution of Gallardoneris iberica (Polychaeta, Lumbrineridae) in southern Europe. (18th July 2017) - Katsiaras, Nikolaos; Rousou, Maria; Carrera-Parra, Luis F.; Garcia-Gomez, Sergio Carlos; Simboura, Nomiki; Louizidou, Paraskevi; Chintiroglou, Chariton Charles; Martins, Roberto
Abstract : The polychaete Gallardoneris iberica was described in soft-bottom benthic habitats from the Atlantic Iberian Peninsula coasts in 2012. Since then, successive studies have found this species in Spain, Italy and Croatia. The present study is the first to report G. iberica for Greece and Cyprus (42 new records) confirming its wide geographic distribution on southern European coasts. Taxonomic accounts and ecological preferences based on a large survey and review of available literature are being presented. The species was frequently found in habitats characterized by infralittoral muddy sands with variable organic matter and 'Moderate' ecological quality status; nevertheless it was also recorded in coarser and finer sediments, circalittoral mixed sediments, phytal substrates and undisturbed sites. Its relative abundance per sample was always lower than 2%. A review of the available ecological and geographic data of the other Gallardoneris species and a worldwide taxonomic key to Gallardoneris species are provided.